Effects of an anterior cruciate ligament injury prevention program on performance in adolescent female soccer players - Vescovi, J. D.; VanHeest, J. L. (Scandinavian Journal of Medicine & Science in Sports, 2010)
Female soccer players are three times more likely to suffer a non-contact anterior cruciate ligament (ACL) tear compared with male soccer players. Several ACL injury prevention programs have been developed and are used to reduce injury risk. However, to date there is limited information on how such programs affect physical performance. The aim of this randomized controlled study was to investigate the effects of the Prevent Injury Enhance Performance (PEP) program in adolescent female soccer players. Four soccer teams were randomly assigned to an intervention (PEP) or control (CON) group and assessed at baseline, 6 weeks, and 12 weeks on linear sprinting, countermovement jump (CMJ), and two agility tests. A mixed model factorial ANOVA with repeated measures was used to assess for treatment effects on the dependent variables. Improvements in 27.3 and 36.6 m sprint times (<0.10 s) were evident during the first 6 weeks for PEP, but reverted back to baseline values by 12 weeks; there were no changes for 9.1 or 18.2 m sprint times in either group. There was no change in the CMJ height for PEP; however, there was a decrement at 6 and 12 weeks compared with baseline in CON. Performance on the Illinois and pro-agility tests declined in both groups. Our findings demonstrate that improvements in linear sprint performance were small and transient in adolescent female soccer players, and that there was no benefit of the PEP program on CMJ or agility performance. ACL injury prevention programs designed as a structured warm-up routine seem to lack the necessary stimulus to enhance athletic performance.